(untitled) (Italian Journal of Public Health, 2005)
Cesarean section (c-section) rates have been increasing in many countries, and too frequently this rise does not seem to be justified by clinical grounds. To reduce c-section rates and achieve a proportion of 20% is among the goals of the Italian National Health Plan. In the following paper we provide an update on the distribution of rates amongst Italian regions and describe the association between regional hospital volumes and c-section rates. The national c-section rate increased from 31% in 1998 to 36% in 2002. The rates varied among regions and ranged from 20% in the Province of Bolzano to 56% in Campania. A significant association was observed between the regional hospital volumes for deliveries and c-section rates, regions with low hospital volumes performed more c-sections than high volume regions.